Dynamics of Post-Divorce Family Resilience: A Phenomenological Study of Ex-Wives within á¸¤abÄâ€™ibâ€™s Community - Muhammad Sungaidi; Abdul Aziz; Andi Ridwan; Davik Ihsan Purnama; Ikhwan Ansori (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
Divorce within tight-knit socio-religious structures, such as the á¸¥abÄâ€™ib community, often places women in a vulnerable yet unique position. This vulnerability is manifested through both economic and social challenges, driven by prevailing cultural stigmas and restricted access to essential resources. This study aims to analyze the impact of divorce on women's socio-economic resilience and evaluate the effectiveness of á¸¥abÄâ€™ib widow's home facilities in supporting them after divorce. Employing a qualitative method with a purposive sampling-based case study approach, this study involved seven informants, consisting of six divorced women within the á¸¥abÄâ€™ib community and a facility administrator. Data were gathered through in-depth interviews focusing on post-divorce alimony protection and resource accessibility. The informants were selected based on specific criteria: having experienced divorce within the last five years and having utilized the community-provided housing facilities, ensuring an in-depth exploration of their socio-economic resilience. The results show that although widow á¸¥abÄâ€™ib homes provide benefits in the form of housing and social support, economic challenges remain major obstacles, including limited access to jobs, business capital, and skills training. Therefore, a more comprehensive empowerment strategy is needed, including access to skills training, sharia-based business capital, and more inclusive social protection policies. The implications of this study emphasize the importance of collaboration between the government, communities, and the private sector in creating sustainable empowerment programs to improve women's welfare and independence after divorce.